Distributed Robust Cooperative Hierarchical Control for Island Microgrids under Hijacking Attacks Based on Multiagent Systems - Abdollah Mirzabeigi; Ali Kazemy; Mehdi Ramezani; Seyed Mohammad Azimi (International Transactions on Electrical Energy Systems)
Today, eliminating the effects of cyber-attacks is essential for stability and synchronization in island microgrids. In this article, island microgrid has been investigated from the view of multiagent systems and graph theory. This study uses the cooperative distributed hierarchical controller in two primary and secondary layers to control the hijacking cyber-attack in the islanded microgrid. Hijacking attacks’ impact on the control of distributed generators (DGs) has been mathematically formulated, and a suitable controller has been designed. Then, global stability and simultaneous synchronization of the frequency and voltage of the microgrid in the presence of a hijacking attack have been investigated by introducing the new Lyapunov function and proving the appropriate theorems. A case study has been simulated in MATLAB/Simulink in a microgrid. Also the effects of false data injection (and its comparison with the hijacking attack) and the time delay in the communication channel of the controller have been discussed. The theory and simulation results confirm the performance of the designed controller in solving this cyber-attack and other disturbances compared to other controllers.